2015
DOI: 10.1242/jeb.126490
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuous gas-exchange cycle characteristics are differentially affected by hydration state and energy metabolism in gregarious and solitarious desert locusts

Abstract: The termination of discontinuous gas exchange cycles (DGCs) in severely dehydrated insects casts doubt on the generality of the hygric hypothesis, which posits that DGCs evolved as a water conservation mechanism. We followed DGC characteristics in the two density-dependent phases of the desert locust Schistocerca gregaria throughout exposure to an experimental treatment of combined dehydration and starvation stress, and subsequent rehydration. We hypothesized that, under stressful conditions, the more stressre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Depending on the physiological conditions, insects can enter a regime of discontinuous gas exchange, in which the spiracle appears to be randomly switching between the open and closed states. [25][26][27][28][29] The functional significance of this regime is still unclear, but several of the proposed mechanisms require quantitative analysis of diffusive fluxes through the tracheal network. 25 A first step in this direction was made by Lawley et al 30 who proposed and analyzed a one-dimensional diffusion model, in which the absorbing boundary condition at the tube exit was used to describe oxygen consumption by the tissue, and randomly switching boundary conditions at the tube entrance were used to describe the spiracle dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the physiological conditions, insects can enter a regime of discontinuous gas exchange, in which the spiracle appears to be randomly switching between the open and closed states. [25][26][27][28][29] The functional significance of this regime is still unclear, but several of the proposed mechanisms require quantitative analysis of diffusive fluxes through the tracheal network. 25 A first step in this direction was made by Lawley et al 30 who proposed and analyzed a one-dimensional diffusion model, in which the absorbing boundary condition at the tube exit was used to describe oxygen consumption by the tissue, and randomly switching boundary conditions at the tube entrance were used to describe the spiracle dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…A breakdown of the cycle into its burst and interburst phases (figure 1a) revealed that differences in cycle duration resulted from changes in the interburst (t 68 ¼ 3.790, p , 0.001) but not the burst duration (t 68 ¼ 1.119, p ¼ 0.267). Calculation of CO 2 accumulation during the interburst (see [12]), assuming constant cellular metabolic rate despite intermittent gas exchange with the environment, revealed that the selected locusts had evolved a significantly higher capacity to accumulate CO 2 (F 1,68 ¼ 9.763, p ¼ 0.003) (table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we found a significantly higher haemolymph protein concentration in the selected locusts (S.T., 2016, unpublished data), and this important haemolymph buffer in locusts [15] may aid in alleviating acid-base balance alterations resulting from CO 2 accumulation. Interestingly, locust density-dependent phase-specific variations in haemolymph protein content were also associated with changes in DGE properties in the desert locust, Schistocerca gregaria, during desiccation [12].…”
Section: Discussionmentioning
confidence: 96%
“…When crowded, however, locusts express the notorious gregarious phenotype, tending to aggregate into swarms, to migrate, and to consume huge amounts of vegetation, thus causing severe damage to agriculture (gregarious phase) [1,3,5,6]. The phase transition from solitary to gregarious in the different locust species encompasses many changes, including a marked behavioral change [5][6][7][8], as well as immense physiological changes [5,6,9,10].…”
Section: Introductionmentioning
confidence: 99%